Between Baltimore 1915 and Barcelona 1968- Historical continuities in the first congress of the profession in Spain - Lombardero Posada, Xoán (Cuadernos de Trabajo Social, 2025)
In 1968, Spanish social work chose foundational themes related to the professional literature of the time. These topics, in turn, are linked to central concerns of the profession in the United States, dating back to events in 1915 and 1957. This paper explores in detail the key aspects of these debates, as well as the organizational forms in which they took place. Despite the geographic and temporal distance, the materials analyzed reveal a shared professional ethos and connection on both sides of the Atlantic.
Keywords: social work history; Abraham Flexner; 1955 NCCC conference; Ernest Greenwood; FEDAAS